STRATEGI PENGELOLAAN RISIKO RANTAI PASOK KOMODITAS KENTANG DI KABUPATEN BANDUNG - Inggit Riszia Pernanda; Akhmad Riyadi Wastra; Akhmad Mahbubi (Departement of Agribusiness Faculty of Science and Technology, 2018)
This study aims to: (1) Know flowchart potato supply chain in Bandung regency. (2) Identify the risks arising from potato supply chain in Bandung regency. (3) Measure the risk at each level of the supply chain. (4) Map the risk. (5) know the way of farmers risk management, collectors and distributors in Bandung regency. This study uses a fish bone, Approximations, and Matrix Chart. The management of risk will determine by avoiding, controlling, transferring, and accepting the risk. The results of this study show risks of 20 per event at the farm level, 7 per event risk at the level of the collector and 10 per event at the distributor level. Based on the measurements of approximation methods are show the highest value at the farm level, then the distributor, and the lowest for the collector. Based on the mapping of the level of farmers and distributors located in quadrant I, while the level of collection is located in quadrant IV. Based on management priorities, held by avoiding, mitigating, transferring, keeping risks, shows there are 26 mitigation actions that can be realized to reduce the causes of such risks.